Comparison of oral pre-medication with clonidine and metoprolol on intraoperative hemodynamics and surgical conditions during functional endoscopic sinus surgery - Urmila Keshari,; Sonali Gupta,; Neelesh Nema,; Sherin Soni,; Richa Pandey, (Asian Journal of Medical Sciences, 2024)
Background: Functional endoscopic sinus surgery (FESS) is one of the most performed surgical procedures and requires minimal bleeding during the procedure. The success of surgeries is largely dependent on the surgical field, where the presence of significant bleeding is an important factor. Aims and Objectives: The objectives of this study were to evaluate the clinical efficacy of oral clonidine and metoprolol following their pre-medication for induced hypotension during FESS and to assess hemodynamic stability, surgical field quality, and sedation score. Materials and Methods: This is an observational hospital-based study conducted on 60 patients, aged 18–60 years old for FESS assigned by randomization method in two groups including clonidine or metoprolol. Heart rate (HR) and arterial blood pressure are measured after induction, during and end of the surgery. Assessment of bleeding was done by a surgeon who was blinded. Surgical field quality, satisfaction level of the surgeon, Aldrete score, and any side effects were observed. Results: There was no significant difference seen in HR in patients of Group C and Group M in the pre-operative period, after loading the dose of the drug, at extubation (P>0.05). A significant difference was seen in HR with lower mean values in Group C compared to Group M after induction (77.23±12.23), 10 min after induction (69.47±11.99), 20 min after induction (65.63±8.66), 30 min after induction (64±8.32), 40 min after induction (63.77±7.61), and 60 min after induction (63.63±7.89). A significant difference was seen in blood pressure, after loading the dose of the drug, after induction, during surgery monitored every 10 min, at extubation, after extubation monitored every hour for 6 h. Quality of surgical field and surgeon’s satisfaction was better in patients who received clonidine than in those who received metoprolol. Conclusion: Both clonidine and metoprolol can be effectively used for induced hypotension in FESS. Clonidine is better than metoprolol with respect to intraoperative hemodynamics, quality of the surgical field, and surgeon’s satisfaction with the added advantage of sedation, reduced analgesia requirement, and other anesthetic drugs.